1998
DOI: 10.1046/j.1365-2249.1998.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 receptor blockage inhibits the onset of autoimmune kidney disease in NZB/W F1 mice

Abstract: In the present study, we examined the preventive effect of anti-mouse IL-6 receptor (IL-6R) antibody, MR16-1, on the development of autoimmune kidney disease in female NZB/W F1 (BWF1) mice. Immunological tolerance to MR16-1 or isotype-matched control antibody, KH-5, was induced by the simultaneous administration of anti-CD4 MoAb in mice. Thereafter, mice were intraperitoneally given 0.5 mg of MR16-1, 0.5 mg of KH-5 or saline once a week from 13 to 64 weeks of age. MR16-1 treatment dramatically suppressed prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 28 publications
0
94
0
6
Order By: Relevance
“…These studies emphasize the importance of steady-state levels of IL-6 for responses to infection, as well as the ability of IL-6 to cause severe immunopathology when expressed at high levels. Given the long association between IL-6 and SLE (36,37,(46)(47)(48)(49), it is surprising that there are very few studies that have targeted the IL-6 axis in SLE, and no significant clinical trials using anti-IL-6 (tocilizumab), even though targeting of IL-6 has been shown to be successful in the treatment of autoimmune-prone animals (50)(51)(52). This is particularly surprising given that therapies targeting IL-6 have been shown to be very effective in the treatment of other autoimmune diseases such as rheumatoid arthritis (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…These studies emphasize the importance of steady-state levels of IL-6 for responses to infection, as well as the ability of IL-6 to cause severe immunopathology when expressed at high levels. Given the long association between IL-6 and SLE (36,37,(46)(47)(48)(49), it is surprising that there are very few studies that have targeted the IL-6 axis in SLE, and no significant clinical trials using anti-IL-6 (tocilizumab), even though targeting of IL-6 has been shown to be successful in the treatment of autoimmune-prone animals (50)(51)(52). This is particularly surprising given that therapies targeting IL-6 have been shown to be very effective in the treatment of other autoimmune diseases such as rheumatoid arthritis (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…60 Antibodies were applied in doses previously shown to be effective, including anti-IL-6R (750 mg, MR16-1; provided by Chugai Pharmaceutical Co. Ltd., Tokyo, Japan 33 ), anti-IL-6 (500 mg, MP5-20F3), and sgp130Fc (250 mg), 61 or control antibodies (750 mg rat IgG for MR16-1 or 500 mg hIgG for anti-IL-6 and sgp130Fc) were intraperitoneally injected 24 hours before and 5 days after NTN induction. For aNTN, 41 mice were preimmunized with sheep IgG in complete Freund's adjuvant at day 5.…”
Section: Animal Experiments and Functional Studiesmentioning
confidence: 99%
“…32 Application of anti-IL-6R as well as anti-IL-6 antibodies were subsequently shown to ameliorate disease by two independent groups. 33,34 Mechanistically, the deleterious effects of IL-6 were largely ascribed to production of pathogenic antibodies. Some authors also suspected IL-6 effects on T-cell activation; however, this was not addressed any further and effects on Th17 responses have not yet been studied.…”
mentioning
confidence: 99%
“…Mice and SLE patients exhibit elevated IL-6 and inhibition of IL-6 or the IL-6 receptor decreases anti-dsDNA and proteinuria. [73][74][75] With HSP90 inhibition by GA, IL-6 expression was reduced in macrophages by preventing HSP90 from chaperoning newly transcripted cytokines. 76 HSP90 complexes with iNOS and is required for iNOS to synthesize NO.…”
Section: Mature B Cells Were Decreased In Mice Treated With 17-dmagmentioning
confidence: 99%